Notoginsenoside R1 Protects Against High Glucose-Induced Cell Injury Through AMPK/Nrf2 and Downstream HO-1 Signaling - Du, Fawang; Huang, Huiling; Cao, Yalin; Ran, Yan; Wu, Qiang; Chen, Baolin (Frontiers in Cell and Developmental Biology, 2021)
Notoginsenoside R1 (NGR1), the primary bioactive compound found in Panax notoginseng, is believed to have antihypertrophic and antiapoptotic properties, and has long been used to prevent and treat cardiovascular diseases. However, its potential role in prevention of diabetic cardiomyopathy remains unclear. The present study aimed to investigate the mechanism of NGR1 action in high glucose-induced cell injury. H9c2 cardiomyocytes were cultured in a high-glucose medium as an in-vitro model, and apoptotic cells were visualized using TUNEL staining. Expression of Nrf2 and HO-1 was measured using Western blotting or reverse transcription-quantitative PCR (RT-qPCR). The Nrf2 small interfering (si) RNA was transfected into cardiomyocytes using Opti-MEM containing Lipofectamine® RNAiMAX. NGR1 protected H9c2 cardiomyocytes from cell death, apoptosis and hypertrophy induced by high glucose concentration. Expression of ANP and BNP was remarkably reduced in NGR1-treated H9C2 cells. Western blot analysis showed that high glucose concentration markedly inhibited Nrf2 and HO-1, and this could be reversed by NGR1 treatment. However, the cardioprotective effect of NGR1 was attenuated by compound C, which reverses Nrf2 and HO-1 expression levels, suggesting that AMPK upregulates Nrf2 and HO-1 gene expression, protein synthesis and secretion. Transfection of H9C2 cells with Nrf2 siRNA markedly reduced the cardioprotective effect of NGR1 via reduced expression of HO-1. These results indicated that NGR1 attenuated high glucose-induced cell injury via AMPK/Nrf2 signaling and its downstream target, the HO-1 pathway. We conclude that the cardioprotective effects of NGR1 result from upregulation of AMPK/Nrf2 signaling and HO-1 expression in cardiomyocytes. Our findings suggest that NGR1 treatment might provide a novel therapy for diabetic cardiomyopathy.